Imágenes bizantinas del s. X en Liutprando de Cremona. Discurso, memoria y poder - Zamora Navia, Patricio (Byzantion Nea Hellás, 2015)
Liutprando of Cremona is, without a doubt, one of the most remarkable writters in 10th century, un West. As ambassador, first of Berengario and after oton 1, he had the opportunity to visit Constantinople.The testimonies of their embassies, consigned in two works - Antapodosis andLegatio -, reveal diverse Byzantine images that, from the point of view of thetheoretical and symbolic analysis of the power, allow severa! interpretativelevels. The author stops in the analysis of the speech that generales the story ofLiutprando, establishing the presence of two categories of power. Theverbalized power whose expression is the adjetival narration of its experienceand the oppositions of images (Oriente/Occidente); and the represented power,embodied in the palace liturgy, essential componen! of the Byzantine kratofanía.